The Role of Pancasila Education Teachers in Instilling Civic Responsibility in Students at SMAN 1 Batukliang - Riska Riska; Muhammad Mabrur Haslan; Sawaludin Sawaludin (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the role of Civic Education teachers in instilling civic responsibility among students and to identify the supporting and inhibiting factors in the process at SMAN 1 Batukliang. The research uses a qualitative approach with a case study design. Data were collected through interviews, participant observation, and documentation involving Civic Education teachers, the principal, vice principal for student affairs, and students. Data analysis follows the Miles and Huberman model, including data reduction, display, and conclusion drawing, with data validity tested through triangulation of techniques, sources, and time. The results show that Civic Education teachers play multidimensional roles as facilitators, classroom managers, mediators, motivators, evaluators, and demonstrators in shaping civic responsibility. Supporting factors include school support, flexible curriculum policies, active teacher participation, and a positive school social environment. Inhibiting factors include students' low awareness of social responsibility, lack of family support, and limited time and innovative learning media.In conclusion, fostering civic responsibility requires a holistic approach involving continuous synergy between schools, families, and communities to develop responsible, caring, and active citizens with strong state responsibility.